Adaptation to mid-season drought in a sweetpotato (Ipomoea batatas [L.] Lam) germplasm collection grown in Mozambique - Makunde, G.S.; Andrade, M.I.; Ricardo, J.; Alvaro, A.; Menomussanga, J.; Grüneberg, W.J. (Walter de Gruyter GmbH, 2017)
Drought has negative effects on sweetpotato production. Two experiments with two watering treatments (irrigated and water-stressed) were conducted at Umbeluzi Research Station in 2015. The objectives were to (i) determine response of 48 sweetpotato germplasms to mid-season drought, (ii) determine best traits for improvement of storage root yield under mid-season drought and (iii) assess the selection criteria for identifying drought tolerance in sweetpotato germplasms. The irrigated and water- stressed trials received 640 and 400 mm of water, respectively, throughout the season. Water stress was imposed from 30 to 70 days after planting. Each treatment had two replicates arranged in a randomized complete block design. Data collected on storage root and vine yield and derived drought tolerance indices including harvest index were subjected to analysis of variance in R. Sweetpotato germplasms with high storage root yield under mid-season drought were associated with a high harvest index. Harvest index stability and the geometric mean are key to identifying cultivars with high and stable storage root yield under both treatments. MUSGP0646-126, Irene and Ivone combined both low TOL, SSI, HI and high yield storage root yield across the treatments and over seasons. The use of drought and harvest indices is encouraged for selecting improved cultivars for varied production environments and their regular use in accelerated breeding schemes is suggested.